Camp Damascus - Tingle, Chuck (New York : Tor Publishing Group, 2023)
"Welcome to Neverton, Montana: home to a God-fearing community with a heart of gold. Nestled high up in the mountains is Camp Damascus, the self-proclaimed 'most effective' gay conversion camp in the country. Here, a life free from sin awaits. But the secret behind that success is anything but holy. And they'll scare you straight to hell"--
"A Tom Doherty Associates Books."
Keywords: Sexual minorities -- Fiction; Camps -- Fiction; Montana -- Fiction; Horror fiction; Queer fiction; LGBTQ+ fiction